2004
DOI: 10.1177/146642400312400112
|View full text |Cite
|
Sign up to set email alerts
|

Some puzzling situations in the onset, occurrence and future of coronary heart disease in developed and developing populations, particularly such in sub-Saharan Africa

Abstract: Coronary heart disease (CHD) was rare in developed populations until the early 1900s; this prevailed even among the small segments who were prosperous and who, in measure, had most of the currently recognised risk factors. However, in the 1930s, with improved circumstances from general rises in socio-economic state, there were major increases in the occurrence and mortality rate from the disease, the latter reaching a third of the total mortality in some countries, as in the United Kingdom (UK). Puzzlingly, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 71 publications
0
22
0
Order By: Relevance
“…1 The growing prevalence of noncommunicable chronic diseases is evident in South Africa as well. [2][3][4] In 2000, physical inactivity was estimated to be the ninth leading cause of deaths in South African adults. The majority of these deaths were attributed to ischaemic heart disease.…”
Section: Introductionmentioning
confidence: 99%
“…1 The growing prevalence of noncommunicable chronic diseases is evident in South Africa as well. [2][3][4] In 2000, physical inactivity was estimated to be the ninth leading cause of deaths in South African adults. The majority of these deaths were attributed to ischaemic heart disease.…”
Section: Introductionmentioning
confidence: 99%
“…1 From the 1930s to the 1950s, the rate of cardiovascular disease increased in high-income countries, but during this period, the rates were low in middle-and low-income countries. 2,3 Since the mid-1970s, the rate of death from cardiovascular diseases has declined markedly in several high-income countries, owing to reductions in risk factors and improved management of cardiovascular disease. 4 By contrast, the incidence of cardiovascular disease has been increasing in some low-income and middle-income countries, 5,6 with 80% of the global burden estimated to occur in these countries.…”
mentioning
confidence: 99%
“…The absence of high quality data relating to AMI in Sub-Saharan Africa, perhaps, makes this assertion speculative. 8,9 We found that our index patient belonged to the high socioeconomic group, has obesity, hypertension, and a sedentary life style, all of which have been reported as predisposing factors to ACS in Nigeria. 4 The diagnosis of AMI usually employs the classic World Health Organization criteria requiring that at least two of the following conditions be present: a) a history of ischemic-type chest discomfort, b) evolutionary changes in serially obtained ECG tracings, and c) a rise and fall in serum cardiac markers.…”
Section: Discussionmentioning
confidence: 79%